Amplitude and energy characteristics of long waves in the Bosphorus Strait - Bazykina, A.Yu.; Dotsenko, S. F. (Reports of the National Academy of Sciences of Ukraine, 2015)
The channel theory of linear long waves is used to calculate the amplitude and the energy of surface waves in their propagation in a channel with variable cross-section. The channel geometry is similar to that of the Bosphorus Strait. The numerical analysis of the maximum wave heights in the strait during the propagation of single waves from the Marmara Sea to the Black Sea and vice versa and the changes of the potential, kinetic, and total energies of the wave field in time is carried out.